Effect of saffron on serum leptin levels in patients with metabolic syndrome, a double-blind, randomized and placebo-controlled trial study - Zilaee, Marzie; Soukhtanloo, Mohammad; Ghayour-Mobarhan, Majid; Shemshian, Maryam; Salehi, Maryam; Ferns, Gordon A.A. (Progress in Nutrition, 2018)
Background: Metabolic syndrome is a risk factor for cardiovascular disease and diabetes mellitus. A decreased level of serum leptin is reported for obese populations. Beneficial effects of saffron on human health, including appetite-regulation, have been reported previously. The aim of this study was to investigating the effect of saffron supplementation on serum leptin levels in patients with metabolic syndrome. Material and method: Patients with metabolic syndrome were randomly divided into two groups; a case group, receiving saffron and a control group, receiving placebo. Concentration of serum leptin was measured at baseline and after 12 weeks of the start of study. SPSS software was used to analyze the data. Results: There was a borderline (p=0.05) significant difference in serum leptin before and after treatment with saffron, but not in the placebo group. There was a significant difference in serum leptin concentrations between the groups (p=0.001). Conclusion: Saffron supplementation has no significant effect on serum leptin levels in patients with metabolic syndrome.